Field Deployment of a Portable Optical Spectrometer for Methane Fugitive Emissions Monitoring on Oil and Gas Well Pads - Eric J. Zhang; Chu C. Teng; Theodore G. van Kessel; Levente Klein; Ramachandran Muralidhar; Gerard Wysocki; William M. J. Green (Sensors, 2019)
We present field deployment results of a portable optical absorption spectrometer for localization and quantification of fugitive methane (CH4) emissions. Our near-infrared sensor targets the 2ν3 R(4) CH4 transition at 6057.1 cm−1 (1651 nm) via line-scanned tunable diode-laser absorption spectroscopy (TDLAS), with Allan deviation analysis yielding a normalized 2.0 ppmv∙Hz−1/2 sensitivity (4.5 × 10−6 Hz−1/2 noise-equivalent absorption) over 5 cm open-path length. Controlled CH4 leak experiments are performed at the METEC CSU engineering facility, where concurrent deployment of our TDLAS and a customized volatile organic compound (VOC) sensor demonstrates good linear correlation (R2 = 0.74) over high-flow (>60 SCFH) CH4 releases spanning 4.4 h. In conjunction with simultaneous wind velocity measurements, the leak angle-of-arrival (AOA) is ascertained via correlation of CH4 concentration and wind angle, demonstrating the efficacy of single-sensor line-of-sight (LOS) determination of leak sources. Source magnitude estimation based on a Gaussian plume model is demonstrated, with good correspondence (R2 = 0.74) between calculated and measured release rates.